2022
DOI: 10.28991/esj-2023-07-01-05
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Concentration and Structure of the Bioeconomy: The Regional Approach

Abstract: The bioeconomy is seen as crucial for achieving a climate-neutral Europe by 2050; therefore, it is important to monitor and illustrate the performance and trends of the bioeconomy development not only at state level but also in regions. The research aims to develop a methodology for the identification of bioeconomy concentration and the structure of bioeconomy enterprises at a regional level. The methodology of the research is based on four main steps: (1) defining the framework of bioeconomy enterprises; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Despite some progress in solving environmental challenges, Latvia (Organisation for Economic Co-operation…, 2022) should do more to achieve green and sustainable economic growth. A study (Muska et al, 2023) revealed that the Latvian bioeconomy is dominated by low-tech industries. Incentives and support tools for entrepreneurs are therefore needed to facilitate the shift from low to medium-high and high-tech use.…”
Section: Common Agricultural Policy Strategic Plan 2023-2027 (2022)mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite some progress in solving environmental challenges, Latvia (Organisation for Economic Co-operation…, 2022) should do more to achieve green and sustainable economic growth. A study (Muska et al, 2023) revealed that the Latvian bioeconomy is dominated by low-tech industries. Incentives and support tools for entrepreneurs are therefore needed to facilitate the shift from low to medium-high and high-tech use.…”
Section: Common Agricultural Policy Strategic Plan 2023-2027 (2022)mentioning
confidence: 99%
“…Those companies that represent the traditional bioeconomy sector and focus on the primary production of bioresources (mainly in agriculture and forestry) operate in the rural administrative territories of Latvia. Thus, it shows the regional economy's dependence on the performance of such companies (Muska et al, 2023). The number of companies working in the field of agriculture in 2021 was 11.6%, but in forestry -only 2.1% of all companies in the market sector (Official Statistics Portal…, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern biotechnologies can be applied in industry, energy, agriculture economy, medicine, ecology etc.Bioeconomy and biotechnology it is the most highly technological part of the economy. In many countries, it has become widespread and developed(Frisvold G. B. et al, 2021;Muska A. et al, 2023;…”
mentioning
confidence: 99%
“…Stratēģijas mērķi ir orientēti uz trim jomām: nodarbinātības veicināšanu un saglabāšanu bioekonomikas nozarēs, bioekonomikas produktu pievienotās vērtības palielināšanu, bioekonomikas eksporta produkcijas vērtības palielināšanu (Latvijas Bioekonomikas stratēģija..., 2017). Bioekonomika ir komplekss un daudzdisciplinārs koncepts, kas definē jaunu pieeju ekonomikas izaugsmē, balstot to uz pētījumiem, inovācijām un iekļaujot sociālo, klimata, enerģijas un resursu efektivitātes pārmaiņu un problemātiku, ar potenciālu veicināt ilgtspējīgu attīstību, tai skaitā pilsētās (Muska et al, 2023). Bioekonomikas stratēģijas mērķis ir veidot ilgtspējīgu attīstību, izmantojot bioresursu potenciālu.…”
Section: Urbānās Lauksaimniecības Aspekti Stratēģiskās Attīstības Dok...unclassified